Future view of safe, painless and curative video assisted thoracoscopic surgery for lung cancer - Nakamura, Katsuya; Miyoshi, Kei; Onishi, Hideya (Video-Assisted Thoracic Surgery; Vol 1 (August 2016): Video-Assisted Thoracic Surgery, 2016)
Before video-assisted thoracoscopic surgery (VATS) became widespread, surgical curability was thought to be the most important issue concerning thoracic surgery; extended surgery was preferred, and postoperative pain did not appear to be a priority. Therefore, only few studies have so far focused on postoperative pain associated with VATS. Although surgical disease curability is important, postoperative pain is also an important issue for patients. Patients will choose to undergo surgery in the institute that can perform both curative and postoperatively painless surgery if possible. Lesser postoperative pain also leads to earlier ambulation and discharge, and could potentially allow earlier initiation of the next stage of therapy (including chemotherapy and radiation) due to faster patient recovery both mentally and physically; this may result in a better outcome.